Calreticulin promotes immunity and type I interferon-dependent survival in mice with acute myeloid leukemia - Chen, Xiufen (Oncoimmunology, 2017)
Exposure of cancer cells to particular chemotherapeutic agents or γ-irradiation induces a form of cell death that stimulates an immune response in mice. This “immunogenic cell death” requires calreticulin (CRT) translocation to the plasma membrane, which has been shown to promote cancer cell phagocytosis. However, it remains unclear whether the effect of CRT on cancer cell phagocytosis is alone sufficient to affect tumor immunity. Acute myeloid leukemia (AML) cells expressing cell-surface CRT were generated in order to characterize the mechanism(s) through which CRT activates tumor immune responses. Potent immune-mediated control or rejection of AML was observed in mice with CRT-expressing leukemia. The “CRT effect” was ultimately T-cell dependent, but dendritic cells (DCs), and CD8α(+) DCs in particular, were also necessary, indicating that CRT might act directly on these DCs. CRT-expressing AML cells were slightly more susceptible to phagocytosis by DCs in vivo, but this effect was unlikely to explain the potent immunity observed. CRT did not affect classical DC maturation markers, but induced expression of type I interferon (IFN), which was critical for its positive effect on survival. In conclusion, CRT functions as a “danger signal” that promotes a host type I IFN response associated with the induction of potent leukemia-specific T-cell immunity.